Arthroscopic Autologous Hamstring Tendon Graft Bridging Repair of an Irreparable Subscapularis Tear - Yongzhi Ye; B.M; Jianmin Zhang, M.D.; Jiehuai Zheng, M.D.; Zhenghua Hong, M.D.; Yang Yang, M.D.; Lingchao Ye, M.D.; Xiaobo Zhou, M.D. (Arthroscopy Techniques)
Irreparable subscapularis tears are technically challenging, but bridging surgery restores the anatomical integrity of the rotator cuff, enabling the residual rotator cuff tissues to regain their functionality. Given the potential benefits of bridging surgeries, we describe a transtendon bridging repair technique that anatomically restores the footprint of the subscapularis, providing a broad area for tendon-to-bone healing. This Technical Note describes this technique and presents a collection of technical insights that could address this specific condition and streamline a potentially daunting surgical process.